Online macroteaching practice of Basic Nursing based on Tencent classroom, MOOC, Rain Classroom and QQ group in the large class (腾讯课堂、MOOC、雨课堂和QQ群"四结合"的大班制护理学基础在线教学实践) - LI Shenmei (李神美); GAO Yan (高燕); DAI Yunyun (戴云云); ZHAO Jia (赵嘉); LIU chunying (刘春英); CHEN Yangguang (陈阳广); PAN Chuang (潘闯); GAN mei (甘媚) (Journal of International Translational Medicine Limited, 2021)
Objective To investigate the application effects of online teaching practice of Basic Nursing based on Tencent classroom, MOOC, Rain Classroom and QQ group. Methods A total of 733 nursing students of academic year 2018 were investigated by online questionnaire, and the effective recovery rate of the questionnaire was 100. 00%. Results The survey found that 12. 01% of the students had noisy classroom environment, the number of students with weak network signal was 20. 05%, 22. 73% of the students thought that the network was the most important factor affecting online learning, 58. 39% of the students had general classroom interaction, 70. 12% of the students thought their autonomous learning ability is average, 63. 98% of the students had general ability to search and integrate information online. 91. 95% of the students were very satisfied with the online teaching mode of "Four Combinations", and their test scores were ideal. Conclusion Students were generally satisfied with the online teaching mode of "Four Combinations", but it was still necessary to improve the online teaching environment, strengthen the effect of classroom interaction and cultivate students' autonomous learning ability. The new online teaching mode of Basic Nursing Courses in macroteaching could provide reference for the effective implementation of online teaching. (目的 探讨腾讯课堂、MOOC、雨课堂和QQ群"四结合"在线教学模式在大班制《护理学基础》理论课中的应用效果。方法 对桂林医学院2018级护理专业学生733人进行"四结合"在线教学, 采用网络问卷调查学生学情。结果 12. 01%的学生认为上课环境是嘈杂的, 20. 05%学生反映网络信号弱, 22. 73%的学生认为网络是影响在线学习最主要的因素; 58. 39%的学生认为课堂互动一般; 70. 26%的学生反映自主学习能力一般; 63. 98%的学生反映网上搜索整合信息能力一般。91. 95%的学生对"四结合"在线教学模式感到非常满意, 本科生考试成绩平均分94. 37分, 高职生考试成绩平均90. 93分, 考核成绩理想。结论 学生对"四结合"的在线教学模式总体满意, 但仍需要改善网络教学环境、加强课堂互动效果和培养学生自主学习能力。通过充分的课前准备、创新教学设计、完善教学评价, 构建的大班制《护理学基础课程》在线教学新模式, 能为有效实施在线教学提供借鉴。)